Persistent low Thyroglobulin Levels with Positive Post therapy Scan in Metastatic Differentiated Thyroid Carcinoma - Ferdous, Jasmin; Bailey, Shamsun Nahar; Akhter, Papia; Islam, Urnas; Mishal, Mohammad Sajjad Al; Sarkar, Shimul; Begum, Fatima (Bangladesh Journal of Nuclear Medicine, 2025)
Background: The level of thyroglobulin (Tg) and 131 I whole-body scan (WBS) are essential for diagnosis of recurrent and persistent differentiated thyroid carcinoma (DTC) after radioactive iodine therapy (RAIT). Low Tg level has high negative predictive value for persistent disease. Tg negative DTC is a rare and diagnostically challenging manifestation within the spectrum of thyroid malignancies that complicates both diagnosis and management. Aim/Objective: This study aims to comprehensively analyze the clinical characteristics, diagnostic approaches, and therapeutic strategies associated with low Tg metastatic DTC and to enhance our understanding of this unusual occurrence. Patients and Methods: A retrospective analysis was conducted on seven diagnosed cases of Tg negative metastatic DTC, who received RAIT from National Institute of Nuclear Medicine and Allied Sciences (NINMAS), and they were selected randomly between the years 2007 to 2023. Patients received RAIT in doses ranging from 150 m Ci to a maximum of 1000 m Ci, given in single to as many as seven therapies. Three patients underwent re-surgery for the removal of metastatic masses. Clinical records, blood profile e.g. stimulated TSH, Tg, Anti TgAb (both initial and latest), imaging studies e.g. ultrasonography (USG), diagnostic whole-body scan (DxWBS)/ large dose scan (LDS), post therapy scan (RxWBS), CT scan, MRI, PETCT, and FNAC, excisional biopsy, histopathology data were systematically reviewed to reveal this specific thyroid carcinoma subtype. Results: A total of seven patients, six males and one female, were referred to NINMAS for RAIT. Age distribution was 30 to 70 years (median: 49 years). The average Tg level was 0.83 ng/ml and anti TgAb was <10.0 IU/ml. Five patients had Papillary Thyroid Carcinoma (PTC) and two had Follicular variant ? (FTC). Four of them presented with metastasis at initial meeting, whereas rest three developed metastasis gradually afterwards. Lymph node (LN) metastasis was noted in four patients, among them two had only cervical LN metastasis, one had cervical and intra-abdominal (para-aortic) nodal metastases, and the last one had inguinal lymph nodes involvement. Three patients had bone metastasis (vertebrae, ribs etc.), one had lung metastasis, one had intra-abdominal mass and one showed chest wall involvement. Metastasis were detected through USG, CT or PET- CT, Bone scan, WBS and later confirmed by histopathology. DxWBS/LDS was done in only three cases, two negative and one positive. Two patients received radiotherapy (RT) for bony involvement. Three patients underwent re-surgery for the removal of metastatic masses. Conclusion: In conclusion, the patient’s symptoms, clinical characteristics, and diagnostic modalities beyond conventional serum markers are needed for accurately identifying and monitoring disease progression in such cases. Bangladesh J. Nuclear Med. 27(2): 202-206, 2024